Study of energy efficient WBAN topology optimization in IEEE 802.15.6 - Zheng-you LIANG; Yu-mei YAO (Tongxin xuebao)
An optimization model was proposed to design the network topology of wireless body area network(WBAN).Focusing on the two hops extended star topology given in IEEE 802.15.6 standard,a mixed integer non-linear programming model was constructed to minimize the energy consumption of WBAN.Then,the optimized network topology was obtained by adjusting the number and location of relays to be deployed and the data routing towards the hub.The experimental results show that,compared with Elias’s model (EAWD,energy aware WBAN design),the proposed model can reduce network energy consumption by 40.5%,decrease network delay by 52.4% on average,and extend network lifetime by double.